THE RELATIONSHIP BETWEEN GESTATIONAL DIABETES MELLITUS (GDM) AND VITAMIN D DEFICIENCY IN PREGNANT WOMEN WITH A BMI BELOW 30 KG/M² - NAEEM , M; RATHI , LL; SARGEIOUS , MM (Biological and Clinical Sciences Research Journal, 2023)
In this study, we aimed to investigate the relationship between vitamin D deficiency and Gestational Diabetes Mellitus (GDM) in women with no significant risk factors for developing GDM. After obtaining approval from the Dubai Scientific Research Ethics Committee, a retrospective cross-sectional study was conducted at the Primary Health Center of the Dubai Health Authority. The electronic medical records system collected data from 200 pregnant women with a BMI of less than 30 kg/m2 who had completed the oral glucose tolerance test (OGTT) and had their vitamin D levels measured between weeks 24 and 28 of gestation. The women were divided into two groups using a random sample procedure. Group A consisted of women with normal serum 25(OH) D concentration (>30.0 ng/mL), while Group B consisted of women with low serum 25(OH) D concentration (<30.0 ng/mL for insufficiency and <10.0 ng/mL for deficiency). The data collected were analyzed using SPSS version 28. Out of the 200 women who met the inclusion criteria, 58 were primigravida (29%), 122 were multigravida 1-3 (61%), 15 were multigravida 4-6 (7.5%), and 5 were multigravida >6 (2.5%). The average age of women in Group A was 24.5±2.4 years, while in Group B, it was 25.0±2.2 years. The average BMI of women in Group A was 26.6±1.5, while in Group B, it was 26.8±2.5. The study’s results revealed that 12% of the women in Group A and 20% in Group B developed GDM (p= <0.01). Our data analysis showed a positive correlation between low vitamin D levels and the development of GDM. However, further large-scale randomized controlled studies are required to establish a causal association between low vitamin D levels and GDM.